2011
DOI: 10.1007/s10211-011-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein content affects the response of meadow voles, Microtus pennsylvanicus, to over-marks

Abstract: The response to signals, including scent marks, from opposite-sex conspecifics can be affected by the nutritional state of both the sender and receiver of these signals. Protein content of the diet affects how meadow voles (Microtus pennsylvanicus) respond to single scent marks, but it is unknown how it affects an individual's response to the overlapping scent marks of two donors (an over-mark). In experiment 1, we tested the hypothesis that protein content of the diet affects the amount of time voles spend in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In addition, pup growth can be affected by maternal dietary protein level (reviewed by Speakman 2008). For males, on the other hand, a high-protein diet has been shown to act as a competitive advantage, as female meadow voles consider scent marks of males on a high-protein diet most attractive (Ferkin et al 1997, Hobbs andFerkin 2011). Consequently, it was surprising that food quality had no detectable effect on maturation and reproduction in either female or male bank voles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pup growth can be affected by maternal dietary protein level (reviewed by Speakman 2008). For males, on the other hand, a high-protein diet has been shown to act as a competitive advantage, as female meadow voles consider scent marks of males on a high-protein diet most attractive (Ferkin et al 1997, Hobbs andFerkin 2011). Consequently, it was surprising that food quality had no detectable effect on maturation and reproduction in either female or male bank voles.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a protein content of 20% and above was found in preferable habitats, often near cultivated areas. Studies that used a similar manipulation of protein content showed that male meadow voles fed with high-protein diets are more attractive to females (Ferkin et al 1997), and further, dietary protein increases males' sexual signaling with scent marks (Hobbs and Ferkin 2011). Meadow voles are considered to be more herbivorous than bank voles (Butet and Delettre 2011), but for the most part their diets are very similar.…”
Section: Climate Chamber Phasementioning
confidence: 99%
“…Scent-marks provide honest signals of health and nutritional status of senders to receivers [ 42 , 43 , 44 ]. Thus, the attractiveness of an individual’s scent marks can vary according to the diet and the amount of food a sender consumes [ 36 , 45 , 46 , 47 ]. Similarly, the receiver’s nutritional state affects its response to the scent marks of opposite-sex conspecifics [ 48 , 49 ].…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…The fact that FD females do not lower their rates of scent marking and over-marking relative to those of AL females suggests that they are not sacrificing opportunities to solicit mates despite facing food deprivation (Hobbs and Ferkin 2011a). However, males voles respond preferentially to the scent marks of AL females compared to those of FD females (Pierce and Ferkin 2005; Pierce et al 2005; Hobbs and Ferkin 2011b). Thus, males may be less interested in seeking out a FD female and mating with her if he also encounters the scent mark of an AL female in the same area.…”
Section: Discussionmentioning
confidence: 96%